Géohistoire du territoire forestier de l’Avesnois : observer le présent, connaître le passé pour anticiper le futur (France) - Marie Delcourte-Debarre (VertigO)
Local management, as Afforestation policy, needs theoretical thesis. Ancient maps were converted into workable data using the SyMoGIH method (Modular System for Historical Data Management). It offers the possibility to work at different scales (territory, landscape, place). Every geographical part of the Avesnois National Park corresponds to a specific space and time data. This method produces an historical analysis for every location of the Park at different times. This method allows to end in an geo-historical analysis of the chosen territory.